Respuesta :

The simplest form of the expression 5(2x-3) - 3(x+4) is 7x  - 27

How to find the simplest form of an expression?

The expression in the simplest form can be found as follows:

5(2x-3) - 3(x+4)

Hence,

5(2x-3) - 3(x+4)

let's open the bracket

Hence,

5(2x-3) - 3(x+4)  = 10x  - 15 - 3x - 12

Therefore,

10x  - 15 - 3x - 12 = 10x  - 3x  - 15 - 12

10x  - 3x  - 15 - 12 = 7x  - 27

Therefore,

5(2x-3) - 3(x+4)  = 7x  - 27

learn more on expression here: https://brainly.com/question/22585971

#SPJ1